ANALISA VOLUME LALU LINTAS DAN PRESENTASE PENGGUNAAN LAHAN PADA RUAS JALAN KADRIE OENING KOTA SAMARINDA - SYAPI'I, MUHAMMAD (KURVA S JURNAL MAHASISWA, 2020)
Samarinda City is the capital of East Kalimantan Province which is a center of economic, educational and even other activities in Samarinda. The Kadrie Oening Road section has a stake to both accommodate and channel movement of traf ic between regions, as well as to have to provide space for traf ic movement for its citizens. The Kadrie Oening Road section has become a busy activity especially at times when there is an increase in high traf ic movements. The theory of the research is peak hour traf ic volume and traf ic speed. Then the modeling used is multiple linear regression with the formula Y = a + B1 X1 + B2 X2 + B3 X3, where the dependent variable that will connect the variable X, a is the intercept and the coef icients B1, B2, B3 are the coef icients of the variables X and XI, X2, X3 are the independent variables. The study carried out in this study was a research conducted on the Kadrie Oening Road section which was divided into 3 segments and carried out during 28 survey days. The survey was conducted from 07.00 - 18.00 and aimed to determine the volume, speed, land area around the 200m wide road, and modeling of the Kadrie Oening Road. Data analysis techniques were performed using linear regression analysis and MKJI 1997. Based on the survey results, the results of the study were obtained, namely peak volume (Q) ranging from 555 pcu / hour to 1247 pcu / hour. With the highest peak volume occurs on Sunday, March 10, 2019. The average speed ranges from 23 km / h to 29 km / h. In analyzing the Kadrie Oening Road section using MKJI 1997, a capacity of 3251 (pcu / hour) and degree of saturation is 0.5235, with modeling for Kadrie Oening Road with linear regression equation Y = 691,009 + (41,756) X1 + 0,221X2 + (- - 36,800) X3, where Y is Traf ic Volume, X1 is the Percentage of Land Area, X2 is Pedestrian, and X3 is Speed.